Islamic Republic of Pakistan : Diagnostic Review of Consumer Protection and Financial Literacy, Volume 2. Comparison with Good Practices - World Bank (Washington, DC, 2014)
The diagnostic review for Consumer Protection and Financial Literacy (CPFL) provides a detailed assessment of the institutional, legal, and regulatory framework in four segments of the financial sector: banking, microfinance, securities, and insurance. The review took place in response to a request for World Bank technical assistance in the field of financial consumer protection made by Pakistan's Ministry of Finance (MoF), the State Bank of Pakistan (SBP), and the Securities and Exchange Commission of Pakistan (SECP). The review consists of two volumes. Volume one summarize the key findings and recommendations of the review and Volume two presents a detailed assessment of each financial segment compared against the good practices for financial consumer protection. The key findings and recommendations in volume one cover five areas: (i) the institutional, legal, and regulatory framework for consumer protection; (ii) disclosure; (iii) business practices; (iv) dispute resolution mechanisms; and (v) financial education. Priority recommendations are outlined in table one; a more detailed list of recommendations is included in annex one.